(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
In this paper a selection of metal objects related to the sphere of household and domestic activities from the Roman villa of S. Cristina in Montichiari (Brescia) is presented and discussed. The typological study of the finds is preceded by an introduction on the area of Montichiari in Roman times and a presentation of the site, currently published only in a preliminary report, whose data are currently being revised. The villa was partly excavated in 1994 in an emergency excavation: two rooms, articulated around a courtyard were found. Almost all the finds, ranging from the Republican period to the early Middle Ages, come from an underground room, which was stripped of its floor and interred; according to a hypothesis here presented, it is possible that the obliteration of this room is related to a transformation of the site’s role and function during the middle Imperial period. Finally, the finds are presented. They consist of fifteen objects, among which are iron keys and knives, lead and bronze objects; some of them belong to widespread forms and types; others, like a lead cover and some objects made of iron and bronze, find no comparisons in the Po plain.